2004
DOI: 10.1152/ajpgi.00355.2003
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular exocytosis contributes to volume-sensitive ATP release in biliary cells

Abstract: Extracellular ATP is a potent autocrine/paracrine signal that regulates a broad range of liver functions through activation of purinergic receptors. In biliary epithelium, increases in cell volume stimulate ATP release through a phosphoinositide 3-kinase (PI3-kinase)-dependent mechanism. Because PI3-kinase also regulates vesicular exocytosis, the purpose of these studies was to determine whether volume-stimulated vesicular exocytosis contributes to cellular ATP release. In a human cholangiocarcinoma cell line,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 36 publications
3
63
1
Order By: Relevance
“…The main ones proposed comprise exocytosis (42) and ATP 4Ϫ translocation via VSOR Cl Ϫ channels at high positive voltages (50). However, as no ATP release was detected in cells stimulated with 200 M H 2 O 2 (a concentration twice the EC 50 for VSOR Cl Ϫ channel activation (22)), our results suggest that ATP is not released through VSOR Cl Ϫ channels.…”
Section: Vsor CLmentioning
confidence: 64%
See 1 more Smart Citation
“…The main ones proposed comprise exocytosis (42) and ATP 4Ϫ translocation via VSOR Cl Ϫ channels at high positive voltages (50). However, as no ATP release was detected in cells stimulated with 200 M H 2 O 2 (a concentration twice the EC 50 for VSOR Cl Ϫ channel activation (22)), our results suggest that ATP is not released through VSOR Cl Ϫ channels.…”
Section: Vsor CLmentioning
confidence: 64%
“…Because the amount of ATP released from swollen cells has been found to be dependent on the magnitude of cell swelling (33,42), we explored the role of P2X4 in VSOR Cl Ϫ channel activity at a smaller hypotonic challenge. As depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is not known whether vesicles mobilized by hypotonic solution contain functional ATP transporters in their membranes. It is interesting to note that by using FM1-43 fluorescence, recent studies have shown that inhibition of PKC or PI 3-kinase in biliary cells blocks both vesicular exocytosis and ATP release [21]. These studies indicate that vesicular exocytosis may contribute to ATP release from biliary cells.…”
Section: Discussionmentioning
confidence: 91%
“…More recent studies have found that pannexin1 hemichannels play a key role in ATP release from many different cells [15][16][17][18]. Vesicular exocytosis may also contribute to ATP release [19][20][21]. Under basal conditions, the concentration of ATP in extracellular media is in a low nanomolar range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation